Investigating the Relationship Between Water Element Designs and User Preferences - Yücel Caymaz, Gökçen Firdevs; Şimşek, Elif (Street Art & Urban Creativity, 2022)
Water elements are design features that complement the environmental landscape with their natural and artificial appearance, particularly in urban spaces. They are effective in boosting the quality of urban space by supporting perceived and real comfort in the area where they are found. In this study, a face-to-face interview photographic survey was conducted with 500 people chosen randomly in five different city squares in Istanbul, whereas participants were asked why they preferred particular water element forms, such as; (natural/geometric form, still / moving form, light / dark colored ground, angular/curvilinear form, natural/colored light). According to the results of the survey conducted, answers provided were grouped under the headings of ‘no reason,’ ‘physical feature,’ ‘psychological effect,’ ‘aesthetic appearance,’ ‘nature conservation,’ ‘modern’ and ‘cleaning.’ As a result of the research, it was observed that water elements with natural forms were preferred over those with geometric forms, water elements with light-colored floors were preferred over those with dark floors, and water elements illuminated with natural light were preferred over those illuminated with colored light. While physical appearance, psychological effect, and aesthetic features of the water elements are the primary factors in the preference of the water element, it was determined that definitions such as cleanliness, nature conservation, and modern appearance are not as influential compared to other selection factors.